(untitled) (Journal of Computational Mathematics, 2002)
In this paper we prove that the solution of explicit difference scheme for a class of semilinear parabolic equations converges to the solution of difference schemes for the corresponding nonlinear elliptic equations in H^1 norm as t→∞. We get the long time asymptotic behavior of the discrete solutions which is interested in comparing to the case of continuous solutions.